Education on Occupational Health and Safety (K3) through K3 Audits as an Effort to Reduce Work Accidents at PT ABC - Rusmiati, Emi; Kramanandita, Ridzky; Ambarwati, Laksmi (Jurnal Pengabdian Masyarakat Bestari, 2024)
Occupational safety and health is something that is important in the work environment. This research is a form of campus community service to the industrial community. Activities are carried out using observational methods, namely observation, education and evaluation of the stages of activity implementation. The results of initial observations and K3 audits, based on data, there are still work accidents, for this reason it is necessary to educate about K3, education is carried out by making pocket books, where with this education there is an increase in knowledge and understanding of K3 which can be shown from the average pretest score of 50 and increased to 74.5.